Pengembangan Alat Evaluasi Pembelajaran Matematika Berbasis Two Tier Multiple Choice Menggunakan Ispring Suite 9 - Chusnul Amalia Rovita; Irwani Zawawi; Syaiful Huda (Universitas Muhammadiyah Gresik, 2020)
In the era of the industrial revolution 4.0 and the pandemic era, innovation is needed in thedevelopment of technology-based evaluation tools. One of them is the ispring suite 9. Evaluation tool isimportant because it can help the process of evaluating educators to find out information on theachievement of results during the learning process. In addition to learning outcomes, evaluation can alsodetermine the ability of students to understand concepts. One of them is a two tier multiple choiceevaluation test. Two tier multiple choice is a form of two-tier multiple choice evaluation test. The purposeof this study is to develop a learning evaluation tool that can find out students' understanding of conceptsand can be used online. The research and development model used is 4D. The research instruments usedwere interview sheets, validation sheets, test instruments, and questionnaires. Data analysis techniquesused qualitative and quantitative. The result of this study is a two-tier multiple choice based mathematicsevaluation tool using ispring suite 9 which is seen from: (1) the percentage of validation results frommedia experts is 90.5% and material experts is 96.5%, both of which fall into the very feasible category.(2) the quality of the items seen from the validity obtained 8 valid items with a reliability of 0.815.Judging from the level of difficulty, the percentage is 10% difficult, 80% moderate and 10% easy, thedistinguishing power is obtained 5 questions are included in the good category, 3 questions are quitegood, 1 question is very good, and 1 question is bad, and the effectiveness of the distractor has 9distractors who selected > 5% of all students. (3) The percentage of students 'conceptual understandingafter evaluating two tier multiple choices is 50.5%, which is in the sufficient category, and the results ofthe students' responses are 82% which is included in the very interesting category.